20.6k views
5 votes
Let m=6x+5m=6x+5m, equals, 6, x, plus, 5.

Which equation is equivalent to (6x+5)^2-10=-18x-15(6x+5)



2



−10=−18x−15left parenthesis, 6, x, plus, 5, right parenthesis, squared, minus, 10, equals, minus, 18, x, minus, 15 in terms of mmm ?

1 Answer

3 votes

We have been given that
m=6x+5. We are asked to rewrite the equation
(6x+5)^2-10=-18x-15 in terms of m.

First of all, we need manipulate right side of our given equation.

We will factor out -3 from right side of equation as:


(6x+5)^2-10=-3(6x+5)

Upon substituting
m=6x+5 in our equation, we will get:


(m)^2-10=-3(m)


m^2-10=-3m

Upon writing this equation in general form of equation, we will get:


m^2+3m-10=-3m+3m


m^2+3m-10=0

Therefore, the equation
m^2+3m-10=0 is equivalent to our given equation.

User AirPett
by
4.9k points